Muc2-dependent microbial colonization of the jejunal mucus layer is diet sensitive and confers local resistance to enteric pathogen infection - George M.H. Birchenough; Bjoern O. Schroeder; Sinan Sharba; Liisa Arike; Christian V. Recktenwald; Fabiola Puértolas-Balint; Mahadevan V. Subramani; Karl T. Hansson; Bahtiyar Yilmaz; Sara K. Lindén; Fredrik Bäckhed; Gunnar C. Hansson (Cell Reports, 2023)
Summary: Intestinal mucus barriers normally prevent microbial infections but are sensitive to diet-dependent changes in the luminal environment. Here we demonstrate that mice fed a Western-style diet (WSD) suffer regiospecific failure of the mucus barrier in the small intestinal jejunum caused by diet-induced mucus aggregation. Mucus barrier disruption due to either WSD exposure or chromosomal Muc2 deletion results in collapse of the commensal jejunal microbiota, which in turn sensitizes mice to atypical jejunal colonization by the enteric pathogen Citrobacter rodentium. We illustrate the jejunal mucus layer as a microbial habitat, and link the regiospecific mucus dependency of the microbiota to distinctive properties of the jejunal niche. Together, our data demonstrate a symbiotic mucus-microbiota relationship that normally prevents jejunal pathogen colonization, but is highly sensitive to disruption by exposure to a WSD.